Constraining XML topic maps with XTche - Librelotto, Giovani Rubert (2005)
This paper presents a process for specifying constraints on topic maps with a constraint language. This language allows to express contextual conditions on classes of Topic Maps. With XTche, a topic map designer defines a set of restrictions that enables to verify if a particular topic map is semantically valid. As the manual checking of large topic maps (frequent in real cases) is impossible, it is mandatory to provide an automatic validator. The constraining process presented in this paper is composed by a language and a processor. The language is based on XML Schema syntax. The processor is developed in XSLT language. The XTche processor takes a XTche specification and it generates a particular XSLT stylesheet. This stylesheet can validate a specific topic map (or a set of them) according to the constraints in the XTche specification. In this paper we will show, in abstract terms and with concrete examples, how to specify Topic Maps schemas and constraints with XTche.